2014
DOI: 10.1039/c4py00529e
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable hybrid selenophene-3,4-ethylenedioxythiophene as electrically conducting and electrochromic polymers

Abstract: A family of four novel selenophene–EDOT oligomers were synthesized using Stille coupling and electropolymerized to form highly stable conducting hybrid polymers with excellent electrochromic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 46 publications
2
40
0
1
Order By: Relevance
“…Generally, they are fabricated from materials that their colors can be changed reversibly by electroredox chemical reactions with small applied voltages [1][2][3][4][5]. Nowadays, organic polymeric materials have been interested to fabricate electrochromic devices based on glasses or flexible substrates [6,7]. Conducting polymer is one of the alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, they are fabricated from materials that their colors can be changed reversibly by electroredox chemical reactions with small applied voltages [1][2][3][4][5]. Nowadays, organic polymeric materials have been interested to fabricate electrochromic devices based on glasses or flexible substrates [6,7]. Conducting polymer is one of the alternatives.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, CVs of PDBF‐3DTh showed an obvious hysteresis, i.e., an obvious potential shift of redox peaks. This phenomenon is hardly explained by conventional kinetic limitations such as ion diffusion or interfacial charge transfer processes . The main reasons are usually slow heterogeneous electron transfer, local rearrangement effect of polymer chains, and electronic charging of interfacial exchange corresponding to the metal/polymer and polymer/solution interfaces .…”
Section: Resultsmentioning
confidence: 99%
“…The surface morphology of PDBT‐3DTh and PDBF‐3DTh deposited on the ITO electrode was investigated by SEM, as shown in Supporting Information Figure S10. PDBT‐3DTh (A) and PDBF‐3DTh (B) films exhibited smooth and compact morphology at high magnifications, which was beneficial to increase the electron transfer capability of conjugated polymer . Also, the smooth and compact morphology of the polymers films were especially significant in the fabrication of electrochromic devices.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that vibronic splitting about conjugated monomers correlate to the rigid structure . Furthermore, the splitted absorption spectra were generally observed in hybrid conjugated samples containing long side chain …”
Section: Resultsmentioning
confidence: 99%